Prognostic Significance of Prolonged Corrected QT Interval in Acute Ischemic Stroke - Ahn, Sung-Ho; Lee, Ji-Sung; Kim, Young-Hak; Yun, Mi-Sook; Han, Jung-Hee; Kim, Soo-Young; Park, Min-Gyu; Park, Kyung-Pil; Kang, Dong-Wha; Kim, Jong S.; Kwon, Sun U. (Frontiers in Neurology, 2021)
Background and Purpose: We aimed to determine the relationship between the heart rate-corrected QT (QTc) interval and the risk of incident long-term mortality in acute ischemic stroke (AIS) patients, especially considering the gender difference as both the decisive factor and a potential confounder in determining thresholds for abnormal QTc intervals in these patients. Methods: We analyzed prospectively registered data included patients with AIS who visited the emergency room within 24 hours of stroke onset and underwent routine cardiac testing, including measurements of cardiac enzymes and 12-lead electrocardiography (ECG). QTc interval was corrected for heart rate using the Bazett formula and was stratified by gender-specific quartiles. Cox proportional hazards models were used to examine the association between baseline QTc interval and incident all-cause death. Results: A total of 1,692 patients with 1034 (61.1%) men and mean age 66.0 ± 12.4 years were deemed eligible. When categorized by quartiles of QTc interval, cardiovascular risk profile and stroke severity increased with prolonged QTc interval, and the risk of long-term mortality increased over a median follow-up of 33 months. Cox proportional hazard model analysis showed that dichotomized QTc interval prolongation, defined by the highest quartile of QTc interval (≥ 459 msec in men and ≥ 475 msec in women; hazard ratio: 1.33, 95% confidence interval: 1.03–1.72) was associated with all-cause death. Conclusions: Prolonged QTc interval was associated with increased risk of long-term mortality in a dose-dependent manner, in parallel with linearly increasing cardiovascular risk profiles and stroke severity, across gender differences in AIS patients.